The Role of Liraglutide and Dapagliflozin in Attenuating Cardio-Renal Injuries in Diabetic Rats - Al-Bana'a, Adel Ali Ali Ali (University of Science and Technology, Sana'a, 2024)
This study aimed to evaluate the therapeutic benefits of dapagliflozin and liraglutide as treatments options for type 2 diabetes mellitus and their combined effects on T2DM-related complications, specifically cardio-renal injuries. Thirty rats were randomly divided into two groups, a control group (n = 6) and an experimental group (n = 24). Rats in experimental group were fed a high-fat diet for four weeks and then injected with a single dose of streptozotocin (STZ) 40 mg/kg i.p. to induce diabetes mellitus (DM). Then, the experimental group was further divided into subgroups a positive control group, a Lira (0.4 mg/kg, s.c.) group, a Dapa (1 mg/kg, orally) group, and a combination of Dapa and Lira group. The treatments were administered daily for four weeks. Blood samples were analyzed for glucose, insulin, and cardiac and kidney function markers. Cardiac and kidney tissue were examined to assess redox homeostasis (malondialdehyde (MDA), glutathione (GSH), and catalase (CAT)). Dapa and/or Lira administration significantly improved the FBG, body weight, lipid profile, and markers of cardiac and kidney function. Furthermore, all treatment groups exhibited restoration of the balance between oxidants and antioxidants. Histological studies also revealed a reduction in cardiorenal tissue injuries caused by diabetes.Z`1 Interestingly, the combined treatment of Dapa and Lira showed a more favorable protective effect compared to individual treatments. These findings suggest that Dapa, Lira, and their combination therapy may be beneficial in protecting against cardiorenal tissue injuries associated with diabetes, highlighting their potential use as adjunctive therapy for managing patients with diabetes mellitus.
Keywords: Liraglutide; Dapagliflozin; Cardio-renal injuries; Diabetic rats; Pharmacology